DETERMINANT ANALYSIS OF ENTREPRENEURIAL INTENTION AMONG MILLENNIAL IN YOGYAKARTA, INDONESIA - Setiartiti, Lilies; Sadik, Nur Azizah Ramadanty (International Journal of Small and Medium Enterprises, 2020)
This study aims to analyze the determinant of millennial entrepreneurial intention in Yogyakarta. The subject in this study was the people resident in Yogyakarta with the age of 19 to 39 years old. Respondents were selected using a purposive sampling method. The data were gathered using questionnaires and analyzed by using multiple linear regression analysis. The finding of this study shows that overall the attitude, perceived behavioral control, family background, entrepreneurial knowledge, and social media have a positive and significant impact on entrepreneurial intention simultaneously. Whereas separately the results show that attitude, behavioral control, family background, and social media have a positive and significant impact on entrepreneurial intention while entrepreneurial knowledge has a negative and insignificant of the millennial generation in Yogyakarta. Overall, this research provides some crucial insights for Yogyakarta’s local government to highlight possible steps for policy makers as a reference for entrepreneurship development.